Ocorrência natural de tripanossomatídeos em morcegos coletados no município de Montes Claros, Minas Gerais, Brasil - Thallyta Maria Vieira (2016)
The bats have great abundance and diversity of species, eating habits and shelters. Because of habitat fragmentation, they have increasingly settled in urban centers. To get to know the possible impacts of the interaction bats / humans and domestic animals, bats were captured from april 2014 to april 2015 in two districts (Vila Luiza and Nossa Senhora das Graças NSG) and in two parks (City Park of Sapucaia CPS) and State Park of Lapa Grande - SPLG) in the city Montes Claros MG. It was done in order to verify the occurrence of trypanosomatids in these animals. It was captured 1,100 bats belonging to the families Emballonuridae (3,5%), Molossidae (10,3%), Phyllostomidae (75,9%), Vespertilionidae, (10,3%). We collected 247 individuals to investigate the presence of trypanosomes. We used NNN cultivation / LIT, with 2.1% (16/741) positive, and 12 stabilized. The isolated ones were identified by the sequencing technique directed to the V7V8 region of SSU rRNA as Trypanosoma dionisii (10/14) and Trypanosoma cruzi (2/14). We also used the PCR SSU rRNA in Leishmania DNA in samples of blood, skin, spleen, liver and bone marrow. For the identification of the species, it was used PCR-RFLP hsp70 with positivity of 4.9% (7/114); four samples were identified as Leishmania braziliensis, but three were not. The 247 DNA samples of blood and the 7 samples positive for the hsp70 target tissue were analyzed by PCR SSU rRNA (V7V8) that detects the Trypanosomatidae family. The positive samples were sequenced for the species identification. The prevalence of infecction by trypanosomatids in the bats collected was of 25,9% (64/247). The genus Leishmania was represented by the species Leishmania amazonensis (9.3%), Leishmania braziliensis (7,8%), Leishmania infantum (4,6%) and Leishmania sp. (4,6%), and the genus Trypananosoma was represented by the species Trypanosoma dionisii (40.6%), Trypanosoma cruzi (4,6%), and Trypanosoma sp. (32,8%). The SPLG park and the NSG district presented the largest number of bats infected by Leishmania sp., suggesting the occurrence of wild and urban cycles of these species. The SPLG and CPS parks had a higher prevalence of species of the genus Trypanosoma, indicating a greater participation of bats in the wild cycle of these parasites. In this study, we found the occurrence of infection of bats by trypanosomatids in different areas of Montes Claros, which is of great ecological and epidemiological importance and of public and animal health.